Local Structure of Ga85:8In14:2 Eutectic Alloy and Its Pressure–Temperature Melting Line. Issue 1 (19th October 2021) - Mijit, Emin; Trapananti, Angela; Nataf, Lucie; Baudelet, Francois; Shinmei, Toru; Irifune, Tetsuo; Jiang, Jian Zhong; Di Cicco, Andrea
Abstract : The structure of the Ga 85.8 In 14.2 eutectic liquid alloy is investigated both under ambient conditions and at high pressure/high temperature using X‐ray absorption spectroscopy (XAS) and X‐ray diffraction (XRD) techniques. The local structure of the liquid alloy at ambient conditions is analyzed using double‐edge refinements of the XAS data. Solid–liquid phase transitions under high‐pressure and high‐temperature conditions are monitored by combined XAS and XRD measurements along several quasi‐isobaric heating runs, allowing to draw a melting line up to 10 GPa. The established melting line is found to be slightly below the one of pure gallium (Ga) and to follow its trend as expected from the eutectic nature of the compound. A series of Ga K ‐edge X‐ray absorption fine structure (XAFS) spectra measured at different pressures indicates the absence of large structural modifications at local Ga sites in the liquid within the investigated pressure and temperature range. Abstract : The local structures in the Ga85.8 In14.2 eutectic liquid alloy at ambient conditions are analyzed with details using double‐edge refinements of the X‐ray absorption fine structure (XAFS). The pressure–temperature melting line of the alloy is established up to 10 GPa using combined X‐ray absorption and diffraction measurements.